Formation of highly oxygenated multifunctional compounds from cross-reactions of carbonyl compounds in the atmospheric aqueous phase. (15th December 2019) - Mekic, Majda; Liu, Jiangping; Zhou, Wentao; Loisel, Gwendal; Cai, Jing; He, Tan; Jiang, Bin; Yu, Zhiqiang; Lazarou, Yannis G.; Li, Xue; Brigante, Marcello; Vione, Davide; et al.
Abstract: There is increasing evidence that aqueous-phase atmospheric chemistry is an important source of secondary organic aerosols (SOA), but this chemistry is currently not adequately represented in atmospheric models due to the missing information on most products. The main focus of this study is to provide molecular-level insight into the photosensitized reaction mechanism of pyruvic acid (PA) alone in the atmospheric aqueous phase, and of mixtures of PA with glyoxal (GL), a typical and widely occurring carbonyl compound. With two ultrahigh resolution mass spectrometers, ORBITRAP and FT-ICR-MS, a broad and complex spectrum of organic products were unambiguously identified. The detected formation of organic compounds illustrates the progression from C3 to C20 molecules through direct PA photolysis and irradiation of PA + GL. The performed ab-initio calculations indicate that cross-reactions (i.e., PA + GL) are more likely than self-reactions (i.e., PA alone) in clouds and aerosol deliquescent particles. Hence, this result implies that photosensitizers like PA can initiate the transformation of common organic cloud constituents like GL into highly oxygenated multifunctional compounds. These high-molecular- weight compounds that are formed in significant amount could potentially impact optical and cloud-forming properties of aerosols, especially if they partition to the aerosol surface. Graphical abstract: Image 1 Highlights: Cross-Reactions between pyruvic acid and glyoxal are favorable in the aqueous phase. ORBITRAP and FT-ICR-MS detected a broad and complex spectrum of organic products. Highly oxygenated multifunctional oligomers are formed during the reaction. The formed oligomers can impact the optical and cloud-forming properties of aerosol.